2014
DOI: 10.1021/ja507918c
|View full text |Cite
|
Sign up to set email alerts
|

Odd-Electron-Bonded Sulfur Radical Cations: X-ray Structural Evidence of a Sulfur–Sulfur Three-Electron σ-Bond

Abstract: The one-electron oxidations of 1,8-chalcogen naphthalenes Nap(SPh)2 (1) and Nap(SPh)(SePh) (2) lead to the formation of persistent radical cations 1(•+) and 2(•+) in solution. EPR spectra, UV-vis absorptions, and DFT calculations show a three-electron σ-bond in both cations. The former cation remains stable in the solid state, while the latter dimerizes upon crystallization and returns to being radical cations upon dissolution. This work provides conclusive structural evidence of a sulfur-sulfur three-electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 78 publications
1
57
0
4
Order By: Relevance
“…17,19 This phenomenon implies the potential influence of hydrogen bonds (H-bonds) on the hemi-bond since charge transfer by orbital overlap frequently occurs with the formation of an H-bond. 20 The influence of H-bonds (solvation) on the hemi-bonded ion core should be explored.…”
Section: Introductionmentioning
confidence: 99%
“…17,19 This phenomenon implies the potential influence of hydrogen bonds (H-bonds) on the hemi-bond since charge transfer by orbital overlap frequently occurs with the formation of an H-bond. 20 The influence of H-bonds (solvation) on the hemi-bonded ion core should be explored.…”
Section: Introductionmentioning
confidence: 99%
“…The MP2/ CBS have been derived using the extrapolations scheme proposed by Helgaker et al [48,49] (Eqs. [1][2][3][4][5]. Here, a = 1.54 and X is the cardinal number associated with the basis sets used: three for aug'-cc-pVTZ and four for aug'-cc-pVQZ.…”
Section: Methodsmentioning
confidence: 99%
“…These clusters can undergo a proton transfer reaction, yielding a cationic molecule and a radical; the resulting monomers might form an isomeric complex [3]. Mainly cationic clusters of chalcogen or halogen atoms have been the subject of such studies [4][5][6][7][8][9][10], while dimers formed by pnicogen atoms have been less reported. The [XH 3 -XH 3 ] Á?…”
Section: Introductionmentioning
confidence: 99%
“…[8] Electrochemical experiments have shown that piano-stool cobalt carbonyl complexes Co 2 Fv(CO) 4 and RCo(CO) 2 (R = Cp or Cp*) could undergo one-electron oxidation to form dimer radical cations in solution, [9] but the radical salts were not isolable due to instability and their crystal structures remain unknown. Recently we have succeeded in stabilization and isolation of radical cations NapE 2 Ph 2 C + (E = S, Se;N ap = naphthalene) that feature aS -S or Se-Se three-electron s bond, [10] which prompted us to investigate the oxidation of transition metal complexes.I nt his paper we report the isolation and crystal structures of cobalt carbonyl radical cations [Co 2 Fv(CO) 4 À were obtained by cooling reaction solutions in CH 2 Cl 2 at À25 8 8C. Thei solated salts are thermally stable under nitrogen atmosphere at room temperature and were studied by single-crystal X-ray diffraction, EPR, IR, and UV/ Visa bsorption spectroscopy,i nc onjunction with DFT calculations.…”
Section: (Co) 2 ]Cmentioning
confidence: 99%
“…Thelong Co-Co bonds in 1C + , 2C + ,and anti-3C + may be rationalized by as imple three-electron bonding model as formed by the interaction of am ono-cobalt radical cation center with lone pair electrons of another cobalt atom, leading to ab ond order of 1/2 or less,a nalogues to threeelectron s-bonds ( Figure S10) of main group elements. [10,17,18] To the best of our knowledge, 2C…”
Section: Anti-3cmentioning
confidence: 99%